The Shield Against Distress: Risk Management as a Mediator of Financial Ratios in the Property Industry - Amiruddin Ahmad; AM Soma (Al-Qalam Institute, 2025)
Financial distress has become a critical issue in the property industry due to the sector’s high dependence on external financing, long project cycles, and vulnerability to economic fluctuations. This study aims to analyze the influence of financial and non-financial ratios on financial distress and to examine the mediating role of risk management in the relationship between these variables. A quantitative approach was employed using panel data regression analysis on property companies, with profitability, liquidity, leverage, sales growth, and company size as independent variables, risk management as a mediating variable, and financial distress as the dependent variable. The results indicate that profitability and liquidity have a significant direct influence on financial distress, suggesting that companies with stronger profitability and adequate liquidity are less likely to experience financial difficulties. Meanwhile, leverage does not directly affect financial distress but exerts an indirect influence through the mediating role of risk management, indicating that effective risk management practices can mitigate the negative impact of high leverage. The findings highlight that financial ratios combined with risk management provide a more comprehensive assessment of corporate financial health. This study contributes to the literature by emphasizing the strategic role of risk management in strengthening financial resilience and reducing the likelihood of financial distress in the property industry, particularly in environments characterized by financial uncertainty and market volatility.